THE CONSEQUENCES OF SECULARISATION IN THE EUROPEAN SOCIETY OF THE XXTH CENTURY - Pukenis, Robertas (European Scientific Journal, ESJ, 2014)
The author describes the forms of secularization and tries to understand the limits of distancing oneself from God. Under certain political circumstances secularization might become very dangerous. Secularization means a process when a human being tries to ‘free oneself’ from religious influence in the society, leaving the religion in a ‘private corner’. The author bravely maintains that the highest liberation from the influence of God can be seen in the philosophy of Nietzsche: it simply ‘killed’ God. Nietzschean philosophy was adopted by Hitler and Europe was ‘liberated in the best way’ from Christian influence by death of million people. The author makes references to well-known historians, proving that both ideologies, rejecting the God, – Marxism and Leninism of Soviet Russia –collaborated with Nazism until the beginning of the World War Two. In short, secularisation can reach its expression in the most radical forms of totalitarian regimes, such as Marxism-Leninism and Nazism. The author has presented a review of godless systems, comparing similarities and differences of Nazism and Communism, and has analysed what lessons modern society can draw out of it.